Evaluation of OUM module content : a pilot study - Shawira Abu Bakar,; Lim , Tick Meng; Rosinah Mahmood,; Loo , Sin Chun (2014)
The module (print or digital) is the main resource used by OUM learners to guide their learning. Therefore, the quality of learning depends greatly on the quality of the module contents. This paper reports on a pilot project that was carried out to evaluate OUM modules for the purpose of improvements. A survey was conducted to gather feedbacks from the users of OUM’s modules which include both learners and tutors. The survey questionnaire seeks to obtain information on the perceptions of the users on the quality of the modules from a number of perspectives. The open-ended questions of the questionnaire also seek to gather information on the different types of errors in the various modules that need to be corrected. Research findings indicate that OUM’s modules are generally well accepted by the users. There are however several errors found in a number of modules. The study helps to identify modules that need to be enhanced. The study also reveals that there are differences in perceptions between the tutors and the learners in certain aspects Some pertinent differences are about the difficulty level of the modules, language used and learning outcomes. (Abstract by author)